2016
DOI: 10.1080/15384101.2016.1192732
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 antagonist suppresses autophagy and lipid droplet growth in adipocytes

Abstract: Obesity and related metabolic disorders constitute one of the most pressing heath concerns worldwide. Increased adiposity is linked to autophagy upregulation in adipose tissues. However, it is unknown how autophagy is upregulated and contributes to aberrant adiposity. Here we show a FoxO1-autophagy-FSP27 axis that regulates adipogenesis and lipid droplet (LD) growth in adipocytes. Adipocyte differentiation was associated with upregulation of autophagy and fat specific protein 27 (FSP27), a key regulator of adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…FOXO1 is an intracellular super transcription factor which modulates numerous cell activities, such as metabolism, apoptosis, and cell circle arrest and maintains tissue homeostasis and changes in response to various stimulations [38,39]. Recent study revealed that FOXO1 positively regulated intracellular lipid droplet formation and growth [40]. Here in our present study, it can be found out that FOXO1 level rose remarkably as lipid droplet accumulated in TECs of SAKI rat model.…”
Section: Discussionsupporting
confidence: 58%
“…FOXO1 is an intracellular super transcription factor which modulates numerous cell activities, such as metabolism, apoptosis, and cell circle arrest and maintains tissue homeostasis and changes in response to various stimulations [38,39]. Recent study revealed that FOXO1 positively regulated intracellular lipid droplet formation and growth [40]. Here in our present study, it can be found out that FOXO1 level rose remarkably as lipid droplet accumulated in TECs of SAKI rat model.…”
Section: Discussionsupporting
confidence: 58%
“…Regulation of the expression and transcriptional activity of FOXO1 is involved in promoting cellular autophagy [7, 30]. In our study, SS condition could upregulate the expression of FOXO1,which regulate both basal and SS-induced autophagy in QBC939 cells.…”
Section: Discussionmentioning
confidence: 57%
“…FoxO1‐specific inhibitor AS1842856 (no. 344355; Sigma‐Aldrich) () was added to a final concentration of 1 u M , and cells were incubated for 24 hours. Cells were then synchronized with 100 n M dexamethasone (no.…”
Section: Methodsmentioning
confidence: 99%